Self-centrality, psychosis and schizotaxia: a conceptual review - Raballo, A.; Lundgren, E.; Leuci, et al., E. (Acta Biomedica Atenei Parmensis, 2006)
The phenomenon of self-centrality denotes a qualitative modification of the psychotic experience. Transitory experiences of self-reference have regularly been found in subjects in the prodromic phase and at the beginning of psychosis or in the post psychotic phase, and are specifically identified in the semeiotics of Basic Symptoms. However, self-centrality, in addition to being a morphological organizer in the psychotic crisis, also manifests itself in schizotypal personality disorders and in first-degree relatives of schizophrenics (where it is correlated to the degree of schizotypal traits). In these subjects, manifestations of self-centrality of a lesser intensity could be an indication of a latent vulnerability trait, which could modulate personal and psychopathological expressions of the schizotaxic diathesis.